2010
DOI: 10.1093/ndt/gfq481
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal colonization as a risk factor for coagulase-negative staphylococcal catheter-related bloodstream infections in haemodialysis patients

Abstract: This study shows that ECC may predict the risk of developing CRSBI. Surveillance cultures could, therefore, be used to triage individual HD patients who might benefit from specific intervention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
23
1
2
Order By: Relevance
“…10 Although we found a significantly lower colonization rate of the CCCs citrate compared with the Tego sodium chloride lock system, we could not demonstrate a reduction of CRBSIs. However, our study was not designed to detect CRBSI; data about CRBSI were collected retrospectively, and the CRBSI rate was very low in all 3 groups (overall, 0.21 CRBSIs per 1,000 catheter-days).…”
Section: Discussioncontrasting
confidence: 71%
“…10 Although we found a significantly lower colonization rate of the CCCs citrate compared with the Tego sodium chloride lock system, we could not demonstrate a reduction of CRBSIs. However, our study was not designed to detect CRBSI; data about CRBSI were collected retrospectively, and the CRBSI rate was very low in all 3 groups (overall, 0.21 CRBSIs per 1,000 catheter-days).…”
Section: Discussioncontrasting
confidence: 71%
“…In recent years, however, they have been related to important nosocomial infections, mainly in weakened and elderly patients and low-weight infants. (15,16) In addition, some species produce a slime layer of polysaccharides that increases the bacterial adhesion to the different surfaces and is related to the formation of biofilms. (17,18) The susceptibility profile of the Staphylococcus revealed that, of all isolated strains, 61.5% were oxacillin-resistant.…”
Section: Discussionmentioning
confidence: 99%
“…(16) . Outro estudo com população de 51 pacientes que fizeram uso de 64 cateteres, 21 desenvolvem ICS (18) . O terceiro estudo encontrou uma taxa global de infecção de 62,8% (IC 95%, 50,4-75, 1%) em uma população de 54 pacientes em hemodiálise por CVC (19) .…”
Section: Estudo Quase Experimental (Não Se Aplica)unclassified
“…A vigilância microbiológica de rotina mostrou-se efetiva e essa estratégia pode ser utilizada para prever possíveis infecções relacionadas ao cateter, embora outros estudos sejam necessários para avaliar o custo-efetividade dessa estratégia (18) .…”
Section: Em Um Dos Estudos As Infecções Por S Aureusunclassified